Analysis of Chicken Cultivation Improvement Strategy in Increasing Family Income: Case Study of Multi Business Livestock - Sitorus, Riska Wulandari; Nuruljannah, Nuruljannah; Syahbudi, Muhammad (Newinera Publisher, 2024)
This study examines the application of SWOT analysis to the MARS free-range chicken business, focusing on strategies to improve competitiveness and sustainability in the poultry industry. By identifying internal strengths, such as the high quality of free-range chickens and a strong consumer reputation, alongside weaknesses like high operational costs and inefficient production, this study formulates actionable strategies for business growth. External factors such as increased market demand for organic chicken and potential government support offer significant opportunities, while price competition and strict regulations pose notable threats. The study applies an SO (Strengths-Opportunities) strategy, recommending the business leverage its strengths to exploit emerging market opportunities, such as expanding online sales and partnerships with halal shops. Additionally, addressing weaknesses by adopting modern cultivation technology and engaging in government-supported programs is suggested to boost production efficiency and market reach. This research fills gaps in existing literature by providing a practical framework for small-scale poultry businesses to adapt and grow in a highly competitive market, especially in regions with rising demand for organic and halal products. The findings offer valuable insights for similar agricultural businesses seeking to optimize their operations and expand their consumer base.